From the editor - Grabowski, Jan; Editors (Zagłada Żydów. Studia i Materiały, 2008)
Writing about the history of the Holocaust in Poland, and in Polish, carries with it a very peculiar set of duties, obligations and challenges. There are few issues in Polish history that reverberate through the nation with such force and whose ongoing discussion is able to have an immediate and profound impact on the national self-perception. The recent discussions surrounding the publication of Jan T. Gross’s books are convincing proof of that. On the other hand, the issues related to the destruction of the Polish Jewry have been among the most forgotten, falsified and manipulated events of the recent past. As discussed in recent decades, the Holocaust became an addition to, rather than an essential and defining part of, Polish historical writing. And these were the reasons why the Polish Centre for Holocaust Research was created in the first place. The members of the Centre set out to return the history of the Holocaust to the centre of the historical focus while, at the same time, trying to make it an integral and inalienable part of mainstream Polish history.